A novel heterozygous STAT5B variant in a patient with short stature and partial growth hormone insensitivity (GHI). (February 2020) - Ramírez, Laura; Sanguineti, Nora; Scaglia, Paula; Keselman, Ana; Ballerini, María Gabriela; Karabatas, Liliana; Landi, Estefanía; Castro, Julia; Domené, Sabina; Pennisi, Patricia; Jasper, Héctor; Rey, Rodolfo A.; et al.
Abstract: Background: The most frequent monogenic causes of growth hormone insensitivity (GHI) include defects in genes encoding the GH receptor itself ( GHR ), the signal transducer and activator of transcription ( STAT5B ), the insulin like-growth factor type I ( IGF1 ) and the acid-labile subunit ( IGFALS ). GHI is characterized by a continuum of mild to severe post-natal growth failure. Objective: To characterize the molecular defect in a patient with short stature and partial GHI. Patient and methods: The boy was born at term adequate for gestational age from non-consanguineous normal-stature parents. At 2.2 years, he presented proportionate short stature (height −2.77 SDS), wide forehead and normal mental development. Whole-exome analysis and functional characterization (site-directed mutagenesis, dual luciferase reporter assay, immunofluorescence and western immunoblot) were performed. Results: Biochemical and endocrinological evaluation revealed partial GH insensitivity with normal stimulated GH peak (7.8 ng/mL), undetectable IGF1 and low IGFBP3 levels. Two heterozygous variants in the GH-signaling pathway were found: a novel heterozygous STAT5B variant (c.1896G>T, p.K632N) and a hypomorphic IGFALS variant (c.1642C>T, p.R548W). Functional in vitro characterization demonstrated that p.K632N-STAT5b is an inactivating variant that impairs STAT5b activity through abolished phosphorylation. Remarkably, the patient's immunological evaluation displayed only a mild hypogammaglobulinemia, while a major characteristic of STAT5b deficient patients is severe immunodeficiency. Conclusions: We reported a novel pathogenic inactivating STAT5b variant, which may be associated with partial GH insensitivity and can present without severe immunological complications in heterozygous state. Our results contribute to expand the spectrum of phenotypes associated to GHI. Highlights: We report a patient with short stature and partial GH insensitivity. A novel heterozygous mutation (p.K632N) in STAT5B was identified using WES. The mutation impairs STAT5b phosphorylation, nuclear translocation and activity. Our study broadens mutation spectrum of STAT5B gene and GHI.